Arab american adolescent perceptions and experiences with smoking - Kulwicki, Anahid (2003)
The purpose of this pilot study was to gather information on Arab American adolescent tobacco use behavior. This information was used to modify the Project Toward No Tobacco Use cessation program so that it would reflect the cultural values of Arab American youths. Focus group interviews were conducted to collect qualitative data from 28 Arab American adolescents between the ages of 14 and 18 years. The number of participants in the focus groups ranged from three to eight; four sessions were conducted. A moderator, fluent in Arabic and English, facilitated the group's interactions. Each group addressed five interview questions. Discussions were audiotaped and transcribed with the expressed permission of study participants. Qualitative analysis consisted of careful reading of the transcripts and of the field notes for the purpose of identifying recurring themes around tobacco use. Those that emerged were Being Cool; Being able to “Nshar ma'a al shabab” (hang out with the guys); Present Orientation; Smoking feels good, tastes good, and keeps your mind off trouble; Availability and Accessibility of tobacco; and Barriers to Smoking Cessation Programs. The results of the focus group discussions provided valuable information about the tobacco use perceptions and behaviors of Arab American adolescents and the youths' need for a culturally relevant smoking cessation program.